Experimental Study of Gap Distance between Floating Structures in Tandem Arrangement - Koto, Jaswar; Siow, C.L. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
This research is proposed to study the effect of wave condition to the distance between floating structures which arranged in tandem arrangement. The evaluation on the gap distance between floating structures is an important study for offshore liquefied natural gas, LNG offloading system because small gap distance between floating structures is needed to guarantee the effectiveness of LNG transfer from FPSO to ship but collision between floating structures should be avoided. Therefore, the gap distance between floating structures becomes a main factor to ensure the safety of the arrangement and effectiveness of the offloading system. Model experiment in regular wave condition was carried out to analyze the motion of floating structures and the effect of wave on changing of gap distance between structures. The time domain motion data are measured by Qualisys Camera and then Fourier Transformation method is applied to transform the data to frequency domain for further analysis. The frequency domain data is utilized in this research to find the tendency of gap distance between floating structures due to the effect of structures response and wave condition. From the study, an empirical equation to simulate the minimum gap distance between floating structures is introduced.